2023
DOI: 10.1007/s11205-023-03109-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Technology on Macro-Level Employment and the Workforce: What are the Implications for Job Creation and Job Destruction in Ghana?

Abstract: Technology whilst creating jobs has destroyed many jobs. The destructive power of technology has led many workers in developing countries, especially Ghana to fight against its introduction. We investigate the effect of technological change on job creation and destruction in Ghana using longitudinal data from the World Development Indicator covering 1990 to 2018. By running the ARDL model, the summative technology-related job destruction is higher in the short run whilst job creation is higher in the long run.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Furthermore, it has facilitated skilled worker mobility, resulting in a more diverse and globalized workforce (Welfens et al, 2020;Zagrodney et al, 2022). Overall, the effects of globalization on the labor market are complex, necessitating thoughtful policies to ensure that benefits are distributed more evenly, and workers are prepared to adapt to a changing job landscape (Asravor, Sackey, 2023;Zheng et al, 2022). Globalization is also kind of the "weapon" for putting pressure on the labor market.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has facilitated skilled worker mobility, resulting in a more diverse and globalized workforce (Welfens et al, 2020;Zagrodney et al, 2022). Overall, the effects of globalization on the labor market are complex, necessitating thoughtful policies to ensure that benefits are distributed more evenly, and workers are prepared to adapt to a changing job landscape (Asravor, Sackey, 2023;Zheng et al, 2022). Globalization is also kind of the "weapon" for putting pressure on the labor market.…”
Section: Discussionmentioning
confidence: 99%
“…While analysing the dualism of job creation-job destruction in a lowincome country (Ghana), it was found that the summative destruction is higher in the short run, but job creation is higher in the long run (Asravor et al, 2023). Cross-European research revealed that the difference between countries in terms of job creation versus job destruction are explained by the country-specific characteristics of ICT investment (non-machine versus machine-based) and the existing skill endowment of the labour force (Marques Santos et al, 2023).…”
Section: Discussionmentioning
confidence: 99%